Comprehensive species- and processing-specific peptide profiling of pasteurized, extended shelf-life and ultra-high temperature milk from cow, goat, sheep, buffalo, and mare - Zenk, Nora; Laumer, Franziska; Dalabasmaz, Sevim; Stützer, Joachim; Mauser, Andreas; Pischetsrieder, Monika (Food Chemistry, 2024)
The present study aimed to identify endogenous milk peptides for species differentiation independent of heat exposure. Thus, comprehensive milk peptide profiles from five species and three types of heat treatments were analyzed by micro-flow liquid chromatography ion mobility quadrupole time-of-flight mass spectrometry (microLC-IM-QTOF) with subsequent database search leading to ≥ 3000 identified peptides. In the milks, 1154 peptides were unique for cow, 712 for sheep, 466 for goat, 197 for buffalo, and 69 for mare. Most peptides were detected in extended-shelf life (ESL) milk (2010), followed by ultra-high temperature (UHT) processed (1474) and pasteurized milk (1459 peptides), with 693 peptides present in all milk types. A blind test set of 64 samples confirmed eight species-specific, but heat-independent marker peptides in milk from cow, seven from goat, six from sheep, nine from buffalo, and three from mare. The generated peptide profiles can also be used to identify species- and heat-specific markers.
CRIS-Team Scopus Importer:2023-12-01
Keywords: Endogenous peptide profiling; Mammalian milk; Marker peptide; microLC-QTOF-MS/MS; Milk heat treatment; Species specification

Enhanced Uptake of Processed Bovine β-Lactoglobulin by Antigen Presenting Cells: Identification of Receptors and Implications for Allergenicity - Teodorowicz, Malgorzata; Zenker, Hannah E.; Ewaz, Arifa; Tsallis, Theodoros; Mauser, Andreas; Gensberger-Reigl, Sabrina; de Jong, Nicolette W.; Hettinga, Kasper A.; Wichers, Harry J.; van Neerven, R. J.Joost; Savelkoul, Huub F.J. (Molecular Nutrition & Food Research, 2021)
Scope: β-lactoglobulin (BLG) is a major cow milk allergen encountered by the immune system of infants fed with milk-based formulas. To determine the effect of processing on immunogenicity of BLG, this article characterized how heated and glycated BLG are recognized and internalized by APCs. Also, the effect of heat-induced structural changes as well as gastrointestinal digestion on immunogenicity of BLG is evaluated. Methods and results: The binding and uptake of BLG from raw cow milk and heated either alone (BLG-H) or with lactose/glucose (BLG-Lac and BLG-Glu) to the receptors present on APCs are analyzed by ELISA and cell-binding assays. Heated and glycated BLG is internalized via galectin-3 (Gal-3)and scavenger receptors (CD36 and SR-AI) while binding to the receptor for advanced glycation end products (R AGE) does not cause internalization. Receptor affinity of BLG is dependent on increased hydrophobicity, β-sheet exposure and aggregation. Digested glycated BLG maintained binding to sRAGE and Gal-3 but not to CD36 and SR-AI, and is detected on the surface of APCs. This suggests a mechanism via which digested glycated BLG may trigger innate (via RAGE) and adaptive immunity (via Gal-3). Conclusions: This study defines structural characteristics of heated and glycated BLG determining its interaction with APCs via specific receptors thus revealing enhanced immunogenicity of glycated versus heated BLG.
CRIS-Team Scopus Importer:2021-03-19
Keywords: aggregation of β-lactoglobulin; cow milk processing; digestion of β-lactoglobulin; galactin-3 Maillard reaction ligands; glycation of β-lactoglobulin; RAGE Maillard reaction ligands

Influence of Software Settings on the Identification Rate, Quantification Results, and Reproducibility in Profiling Post-Translational Modifications by Microflow Liquid Chromatography-Ion Mobility-Quadrupole Time-Of-Flight Analysis Using PEAKS Software - Mauser, Andreas; Gensberger-Reigl, Sabrina; Dalabasmaz, Sevim; Schichtl, Theresa Maria; Dittrich, Daniel; Pischetsrieder, Monika (Journal of Proteome Research, 2024)
The influence of data evaluation parameters on qualitative and quantitative results of untargeted shotgun profiling of enzymatic and nonenzymatic post-translational modifications (PTMs) was investigated in a model of bovine whey protein α-lactalbumin heated with lactose. Based on the same raw data, individual adjustments to the protein database and enzyme settings of PEAKS studio software increased the identification rate from 27 unmodified peptides to 48 and from 322 peptides in total to 535. The qualitative and quantitative reproducibility was also assessed based on 18 measurements of one sample across three batches. A total of 570 peptides were detected. While 89 peptides were identified in all measurements, the majority of peptides (161) were detected only once and mostly based on nonindicative spectra. The reproducibility of label-free quantification (LFQ) in six measurements of the same sample was similar after processing the data by either the PTM algorithm or the LFQ algorithm. In both cases, about one-third of the peptides showed a coefficient of variation of above 20%. However, the LFQ algorithm increased the number of quantified peptides from 75 to 179. Data are available at the PRIDE Archive with the data set identifier PXD050363.
CRIS-Team Scopus Importer:2024-09-27
Keywords: data evaluation; microLC−IM-QTOF; PTM profiling; reproducibility; untargeted proteomics